Double purpose linseed: a viable option for doubling farmers’ income in the north-western Himalyan region - Singh, P. K.; Chopra, Pankaj (Indian Farming, 2018)
Because of favourable climatic conditions there is ample scope for exploiting full potential of dual further strengthening research institutes to standardize the quality parameters for the grading of fibre can certainly reduce the import bills and paves the way for doubling the income of farmers.